FORMULA STRUKTUR NOVEL POPULER INDONESIA PERIODE 1970-1980 - Redyanto Noor; Sukarjo Waluyo; Ary Setyadi (Endogami: Jurnal Ilmiah Kajian Antropologi, 2022)
Since the growth of the Indonesian press industry in the 1970s, popular novels have been carried away by the rapid development of the mass media world. Because, there are facts and data that most of Indonesia's popular novels were originally published as serials in newspapers and magazines. Conclusively, people can classify certain novels into "serious" novels or popular novels. Subjective reasons are not appropriate to be used as criteria to determine certain novels as "serious" novels or popular novels, because the considerations used are only based on personal perception. Of course, this is not scientifically justifiable, because it is not based on clear theories and methods, for example by looking at the intrinsic and extrinsic structures, or also the sociological aspects. Therefore, an inventory of the intrinsic characteristics of popular novels is very important. These characteristics include romantic-sentimental, love and household themes, single plot, straight plot, contemporary dialogue, physical background from a rich family environment, educated family, campus, spectacular and explosive character, anti-double meaning, no need for aesthetic understanding